Gut Microbial Metabolite Pravastatin Attenuates Intestinal Ischemia/Reperfusion Injury Through Promoting IL-13 Release From Type II Innate Lymphoid Cells via IL−33/ST2 Signaling - Deng, Fan; Hu, Jing-Juan; Yang, Xiao; Sun, Qi-Shun; Lin, Ze-Bin; Zhao, Bing-Cheng; Yao, Zhi-Wen; Luo, Si-Dan; Chen, Ze-Ling; Liu, Ying; Yan, Zheng-Zheng; Li, Cai; et al. (Frontiers in Immunology, 2021)
Intestinal ischemia/reperfusion (I/R) injury is a grave condition with high morbidity and mortality. We previously confirmed that intestinal I/R induces intestinal flora disorders and changes in metabolites, but the role of different metabolites in intestinal I/R injury is currently unclear. Based on targeted metabolic sequencing, pravastatin (PA) was determined to be a metabolite of the gut microbiota. Further, intestinal I/R model mice were established through superior mesenteric artery obstruction. In addition, a co-culture model of small intestinal organoids and type II innate lymphoid cells (ILC2s) was subjected to hypoxia/reoxygenation (H/R) to simulate an intestinal I/R model. Moreover, correlation analysis between the PA level in preoperative feces of patients undergoing cardiopulmonary bypass and the indices of postoperative intestinal I/R injury was carried out. IL-33-deficient mice, ILC2-deleted mice, and anti-IL-13 neutralizing antibodies were also used to explore the potential mechanism through which PA attenuates intestinal I/R injury. We demonstrated that PA levels in the preoperative stool of patients undergoing cardiopulmonary bypass were negatively correlated with the indices of postoperative intestinal I/R injury. Furthermore, PA alleviated intestinal I/R injury and improved the survival of mice. We further showed that PA promotes IL-13 release from ILC2s by activating IL-33/ST2 signaling to attenuate intestinal I/R injury. In addition, IL-13 promoted the self-renewal of intestinal stem cells by activating Notch1 and Wnt signals. Overall, results indicated that the gut microbial metabolite PA can attenuate intestinal I/R injury by promoting the release of IL-13 from ILC2s via IL-33/ST2 signaling, revealing a novel mechanism of and therapeutic strategy for intestinal I/R injury.